Ewing's Sarcoma of the Upper Extremity: Presenting Symptoms, Diagnostic Delay and Outcome - Philip M. S. Simpson (Sarcoma, 2005)
Purpose:To look at the presenting features, Enneking stage, size of primary tumour, method of treatment and patient and doctor delays in upper extremity Ewing's sarcoma to observe the effects on local recurrence, metastasis and survival.